Efficacy of cognitive training associated with physical exercises on Alzheimer's dementia: a meta-analysis - Lima Neta, Ana Gonçalves (2020)
Objective: To investigate the effects of cognitive training associated with physical exercise on cognitive performance of elderly people with Alzheimer's Disease (AD). Methodology: A systematic review was carried out with a meta-analysis of controlled and cross-over clinical trials. The literature search was carried out in databases Pubmed / MEDLINE, LILACS, SciELO, PEDro, Scopus, CINAHL and Web of Science, using terms MeSH / DeCS. The risk of bias was assessed according to recommendations of Cochrane Handbook for Systematic Reviews of Interventions and RevMan 5.3 software was used for the meta-analysis. . Results: Initially, 1126 articles were found, nine were chosen for qualitative synthesis and two for meta-analysis. The meta-analysis data showed significant differences in effect size for executive functions and attention, evaluated by Clock Drawing Test (Z = 3.05; p = 0.002) and frontal cognitive functions evaluated by Frontal Assessment Battery (Z = 3.56; p = 0.0004). For qualitative analysis, seven studies demonstrated positive effects of cognitive training associated with physical exercise to improve/maintain cognitive functions of elderly with AD. Conclusion: Despite the limitations found in analyzed studies, it can be suggested that cognitive training associated with physical exercise can benefit the cognitive performance of elderly with AD. However, the dearth of studies developed with greater discerning methodology limits generalizations of these results.